Meet me in Venice : - Ma, Suzanne (Rowman &​ Littlefield, 2015)
When Ye Pei dreamed of Venice as a girl, she imagined a magical floating city of canals and gondola rides. And she imagined her mother, successful in her new life and eager to embrace the daughter she had never forgotten. But when Ye Pei arrives in Italy, she learns her mother works on a farm far from the city. Her only connection, a mean-spirited Chinese auntie, puts Ye Pei to work in a small-town café. Rather than giving up and returning to China, a determined Ye Pei takes on a grueling schedule, resolving to save enough money to provide her family with a better future. A groundbreaking work of journalism, Meet Me in Venice provides a personal, intimate account of Chinese individuals in the very act of migration. Suzanne Ma spent years in China and Europe to understand why Chinese people choose to immigrate to nations where they endure hardship, suspicion, manual labor and separation from their loved ones. Today all eyes are on China and its explosive economic growth. With the rise of the Chinese middle class, Chinese communities around the world are growing in size and prosperity, a development many westerners find unsettling and even threatening. Following Ye Pei's undaunted path, this inspiring book is an engrossing read for those eager to understand contemporary China and the enormous impact of Chinese emigrants around the world.